Site-Specific Gene Knock-Out and On-Site Heterologous Gene Overexpression in Chlamydomonas reinhardtii via a CRISPR-Cas9-Mediated Knock-in Method - Kim, Jongrae; Lee, Sangmuk; Baek, Kwangryul; Jin, EonSeon (Frontiers in Plant Science, 2020)
Chlamydomonas reinhardtii is being transformed from a model organism to an industrial organism for the production of pigments, fatty acids, and pharmaceuticals. Genetic modification has been used to increase the economic value of C. reinhardtii. However, low gene-editing efficiency and position-effects hinder the genetic improvement of this microorganism. Recently, site-specific double-stranded DNA cleavage using CRISPR-Cas9 system has been applied to regulate a metabolic pathway in C. reinhardtii. In this study, we proved that site-specific gene expression can be induced by CRISPR-Cas9-mediated double-strand cleavage and non-homologous end joining (NHEJ) mechanism. The CRISPR-Cas9-mediated knock-in method was adopted to improve gene-editing efficiency and express the reporter gene on the intended site. Knock-in was performed using a combination of ribonucleoprotein (RNP) complex and DNA fragment (antibiotics resistance gene). Gene-editing efficiency was improved via optimization of a component of RNP complex. We found that when the gene CrFTSY was targeted, the efficiency of obtaining the desired mutant by the knock-in method combined with antibiotic resistance was nearly 37%; 2.5 times higher than the previous reports. Additionally, insertion of a long DNA fragment (3.2 and 6.4 kb) and site-specific gene expression were analyzed. We demonstrated the knock-out phenotype of CrFTSY and on-site inserted gene expression of luciferase and mVenus at the same time. This result showed that CRISPR-Cas9 mediated knock-in can be used to express the gene of interest avoiding position-effects in C. reinhardtii. This report could provide a new perspective to the use of gene-editing. Furthermore, the technical improvements in genetic modification may accelerate the commercialization of C. reinhardtii.